Attributes and Knowledge of the Lead Organizer in Planning a Virtual Teacher Professional Development Series: The Case of the Organizer of the Schoolyard Network - Michael Daiga; Mackenzie Hessick (Education Sciences)
Teacher professional development opportunities are woven into the structures of license renewal and school expectations, but the opportunity to profoundly develop in a professional and broad manner is still often a struggle for educators because of financial and time-oriented constraints. The Schoolyard Network is a professional development series of virtual meetings conducted by the Great Smoky Mountains Institute at Tremont to support participating educators in exploring outdoor learning opportunities with K–12 students. This key case study describes the Schoolyard Network’s lead organizer’s knowledge and perspective of running this exemplary case of a virtual outdoor experience platform. Findings suggest that the utilization of an outdoor, experiential, inquiry-based design, while prioritizing mindfulness and conversational techniques such as active listening, reflection, and relationship building are effective design principles for virtual teacher professional development, albeit through a complex, unique system. A model of impact suggests that the Schoolyard Network structure provides meaningful STEM experiential learning activities for educators impacting classrooms across a broad range of environments and geographic proximity.